Experimental study on the physico-mechanical properties and microstructure of foam concrete mixed with coal gangue. (12th December 2022) - Zhang, Xin; Feng, Xiaoping; Wang, Zhenping; Jian, Junchang; Chen, Shuo; Luo, Wei; Zhang, Cong
Highlights: The low CG content can improve the mechanical properties of foam concrete. The content of CG is the key factor affecting the porosity of foam concrete. SEM was used to verify the effect of coal gangue on the microstructure of sample. Abstract: Coal seam fires are a significant disaster in coal mine production. In order to prevent spontaneous coal combustion, it is necessary to build airtight walls in areas such as mined-out areas or working face roadways. Coal gangue (CG) is a solid waste produced in coal mine production, causing ecological damage and resource waste. So in this paper, a coal gangue lightweight foam concrete is developed for confined filling in coal mines. The effect of water-binder ratio(w/b), CG content, fly ash(FA) content, and foam content on the compressive strength, dry density, water absorption, and porosity of coal gangue foam concrete was analyzed in the single-factor and orthogonal experiment. It was found that the w/b and foam content were the two factors with a more significant effect on the mechanical properties of the specimens. For the porosity of the specimens, the amount of CG content is the critical factor that affects them. A scanning electron microscope (SEM) analyzed the specimen's microstructure and observed its pore structure. It was found that the amount of CG content would significantly affect the specimen's microstructure. When the CG content was 30%, the specimen had the best performance index of pores and poor connectivity between pores. This study shows that the foam concrete mixed with CG can have good mechanical properties and pore structure, making a valuable reference for the coal gangue foam concrete for the confinement filling treatment in mined-out areas or working face roadways mines.